2021
DOI: 10.12968/johv.2021.9.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Organising health visiting services in the UK: Frontline perspectives

Abstract: The organisation of health visitor work is an important part of service design, which can have an impact on when and where services are provided and who gains access. This article reports a 2018 survey of UK health visitors conducted to provide an overview of the range of ways in which health visitor cases and workloads are organised. The 584 respondents confirmed the operation of three broad types of health visitor service delivery models; namely, the individual case, the corporate case and the combination mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…Maternal mental and physical health problems would normally lead to primary care intervention in the NHS in England. However, recent reports have suggested that the universal health service has been compromised and general and nurse practitioner services have become less accessible for some families (Whittaker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal mental and physical health problems would normally lead to primary care intervention in the NHS in England. However, recent reports have suggested that the universal health service has been compromised and general and nurse practitioner services have become less accessible for some families (Whittaker et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local authorities and their provider partners have faced funding cuts, low numbers of health visiting staff and high levels of family need, putting pressure on the service [4,[6][7][8]. Case studies and surveys have shown that local authorities have responded differently to these challenges, leading to variations in models of service delivery, priorities, and capacity [2,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…While the objectives of the universal CHPs across the four nations of the UK are similar, there is considerable variation in how they are organised and delivered 2. For example, there is variation in the number and intensity of core contacts between families and services, where those contacts may take place and who should undertake them 3. While models of health visiting can be found elsewhere, the policy contexts influencing service commissioning, delivery, organisation and nursing/professional education differ significantly across countries 4…”
Section: Introductionmentioning
confidence: 99%